AB0261 Matrix Metalloproteinase-3 as A Biomarker of Histological Synovitis in Rheumatoid Arthritis. (10th June 2014) - Ma, J.-D.; Mo, Y.-Q.; Chen, L.-F.; Zheng, D.-H.; Zhu, L.-J.; Dai, L.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic synovitis which leads to bone destruction. Matrix metalloproteinase (MMP) 3 can activate other MMPs, degenerate extracellular components and aggravate inflammation. Previous studies have reported correlation of serum MMP-3 and clinical disease activity in RA. However, little was known about the relationship between MMP-3 and histological synovitis. Objectives: To explore the correlation of serum and synovial MMP-3 and histological synovitis in RA. Methods: Sixty-two patients with active RA were recruited and their serum MMP-3 was detected by ELISA. Synovial tissues were obtained from RA patients as well as 12 OA and 8 orthopedic arthropathies (Orth.A) patients. Serial tissue sections were stained with H&E and immunohistochemically for MMP-3, CD3, CD20, CD38, CD68, CD15 and CD34. Krenn's synovitis score was assessed semi-quantitatively and the density of positive-staining cells were quantitatively determined. Results: (1) In RA synovium, MMP-3 expressed strongly in the endochylema of lining cells (both macrophage-like and fibroblast-like synoviocytes) with absence in the sublining area and the percentage of MMP-3+ lining cells (median 47%, IQR 39–52%) was significantly higher than that in OA (median 20%, IQR 17–24%, P<0.001) or in Orth.A (median 5%, IQR 0–15%, P<0.001, Fig.1 ). (2) According to synovitis score, RA patients were divided into high grade (>4, n=27) and low grade (≤4, n=35) synovitis. The percentage of MMP-3+ lining cells in patients with high grade synovitis was significantly higher than that in patients with low grade synovitis (median 51%, IQR 47–56% vs median 42%, IQR 36–49%, P<0.001). Spearman's rank order correlation test showed significant correlations between the percentage of MMP-3+ lining cells with synovitis score, including total score (r=0.574), hyperlasia of lining layer (r=0.434), inflammatory infiltration score (r=0.272), activation of synovial stroma score (r=0.546), and inflammatory cells in sublining area, such as CD3+T cells count (r=0.284), CD38+ plasma cells count (r=0.313), CD68+ macrophages count (r=0.563) and CD15+ neutrophils count (r=0.670), all P<0.05. Multivariate stepwise linear regression analysis on synovitis score, with synovial MMP-3 and inflammatory cells as independent variables, revealed that synovial MMP-3 and CD38+ plasma cells were incorporated in the final model (both P<0.05) and they accounted for 47% of total variation in synovitis score. (3) Serum MMP-3 was positively correlated with synovial MMP-3 (r=0.651, P<0.001, Fig.1 ). Serum MMP-3 in RA patients with high grade synovitis was significantly higher than that in patients with low grade synovitis (median 325ng/ml, IQR 233–528ng/ml vs median 207ng/ml, IQR 141–392ng/ml, P=0.024). Spearman's rank order correlation test showed significant correlations between serum MMP-3 with synovitis score (r=0.363) and activation of synovial stroma score (r=0.351, all P<0.05). ROC curve analysis showed that the tradeoff value of serum MMP-3 for distinguishing high grade synovitis in RA was 190ng/ml with sensitivity 93% and specificity 49% (AUC=0.668, 95%CI: 0.532–0.803, P=0.024). Conclusions: Our results implied that MMP-3 is involved in synovitis and serum MMP-3 may be a helpful biomarker of histological synovitis. Acknowledgements: This work was supported by Chinese National Natural Science Research Grant (grant no. 81373183 and 81001334), Specialized Research Fund for the Doctoral Program of Higher Education (grant no.20130171110075) and Guangdong Natural Science Foundation (grant no.S2013010014396). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3622